INVENTORY OF FISH SPECIES IN OXBOW TELUK BENDERAS, RANTAU BARU VILLAGE, PANGKALAN KERINCI DISTRICT PELALAWAN REGENCY RIAU PROVINCE - Khoirunisyah, Khoirunisyah; Putra, Ridwan Manda; Efawani, Efawani (Asian Journal of Aquatic Sciences, 2024)
Teluk Benderas Lake is an oxbow lake formed because the Kampar River's flow was cut off. This lake is a habitat for various types of fish. However, information on fish species in the area is still limited. To find out the kinds of fish in Teluk Benderas Lake, a study was conducted in March-May 2023 using the survey method. Fish sampling was performed once a week for two months. The fish were caught using a trawl measuring 150 m long and 4,5 m wide with 1-inch mesh size. Water quality parameters measured were temperature, brightness, depth, pH, DO, and CO2. The results showed that 1.398 fish were caught, consisting of 4 orders, 13 families, 25 genera, and 32 species. Based on the results of water quality measurements, it was concluded that Teluk Benderas Lake can still support fish life in the waters.